Kinetics of Oxidation of Some Amino Acids by N-Chlorosaccharin in Aqueous Acetic Acid Medium - MOHAMED FAROOK, N.A.; HIDHAYATHULLA KHAN, T.; SEYED DAMEEM, G.A. (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of some amino acids e.g., glycine, alanine, aspartic acid, arginine, and histidine, (AA) by N-chlorosaccharin (NCSA) in aqueous acetic acid medium in the presence of perchloric acid have been investigated. The observed rate of oxidation is first order in [AA], [NCSA] and of inverse fractional order in [H+]. The main product of the oxidation is the corresponding aldehyde. The ionic strength on the reaction rate has no significant effect. The effect of changing the dielectric constant of the medium on the rate indicates the reaction to be of dipole-dipole type. Hypochlorous acid has been postulated as the reactive oxidizing species. The reaction constants involved in the mechanism are derived. The activation parameters are computed with respect to slow step of the mechanism.